Blockchain and Cryptocurrencies - Salman, Asma; Abdul Razzaq, Muthanna G. (IntechOpen, 2019)
Finance is the language of business and as technological disruption accelerates, a fundamental change is under way. This presents both opportunities and challenges for current-day organizations and finance professionals alike. Money makes the world go around, they say; but digital money not only makes the world go around, it does it in a decentralized fashion. Because the currencies are decentralized, with the right mix of technology the opportunities that emerge are noteworthy and emerge as a game changer for financial institutions. This book shows many different aspects, examples, and regulations of cryptocurrencies through its underpinning technology of blockchain in the present-day digital era. The diversity of the authors who sum up this book signify the importance of implementation in the digitized economy. It is divided into four main sections, with topics on Bitcoin, blockchain and digital returns, impact of cryptocurrencies in gaming, and cryptocurrency exchanges.